Salmonella enterica Serovar Typhimurium Strategies for Host Adaptation - Anderson, Christopher J.; Kendall, Melissa M. (Frontiers in Microbiology, 2017)
Bacterial pathogens must sense and respond to newly encountered host environments to regulate the expression of critical virulence factors that allow for niche adaptation and successful colonization. Among bacterial pathogens, non-typhoidal serovars of Salmonella enterica, such as serovar Typhimurium (S. Tm), are a primary cause of foodborne illnesses that lead to hospitalizations and deaths worldwide. S. Tm causes acute inflammatory diarrhea that can progress to invasive systemic disease in susceptible patients. The gastrointestinal tract and intramacrophage environments are two critically important niches during S. Tm infection, and each presents unique challenges to limit S. Tm growth. The intestinal tract is home to billions of commensal microbes, termed the microbiota, which limits the amount of available nutrients for invading pathogens such as S. Tm. Therefore, S. Tm encodes strategies to manipulate the commensal population and side-step this nutritional competition. During subsequent stages of disease, S. Tm resists host immune cell mechanisms of killing. Host cells use antimicrobial peptides, acidification of vacuoles, and nutrient limitation to kill phagocytosed microbes, and yet S. Tm is able to subvert these defense systems. In this review, we discuss recently described molecular mechanisms that S. Tm uses to outcompete the resident microbiota within the gastrointestinal tract. S. Tm directly eliminates close competitors via bacterial cell-to-cell contact as well as by stimulating a host immune response to eliminate specific members of the microbiota. Additionally, S. Tm tightly regulates the expression of key virulence factors that enable S. Tm to withstand host immune defenses within macrophages. Additionally, we highlight the chemical and physical signals that S. Tm senses as cues to adapt to each of these environments. These strategies ultimately allow S. Tm to successfully adapt to these two disparate host environments. It is critical to better understand bacterial adaptation strategies because disruption of these pathways and mechanisms, especially those shared by multiple pathogens, may provide novel therapeutic intervention strategies.